1995
DOI: 10.1093/ajcp/104.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Staining for DNA Topoisomerase II in Non-Hodgkin’s Lymphomas

Abstract: DNA topoisomerase II (topo II) is the target of several clinically useful anticancer drugs. Several of these agents, such as doxorubicin and etoposide (VP-16), are used to treat non-Hodgkin's lymphomas (NHL). To understand the therapeutic selectivity of these drugs, a series of 33 cases of NHL for topo II were analyzed using an immunohistochemical technique that detects the enzyme in formalin-fixed, paraffin-embedded tissue. The average topo II index of high grade (Working Formulation) NHL was 48.6 with a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 0 publications
3
38
0
2
Order By: Relevance
“…Meanwhile, topoisomerase II a is highly expressed on aggressive B-cell non-Hodgkin's lymphomas; on the other hand, its expression on T-cell malignancies appears to be generally low, although this conclusion is based on studies with limited samples (Holden et al, 1995;Turley et al, 1997;Korkolopoulou et al, 2001). Our current data with the human T-cell leukaemia cell line Jurkat suggest that the expression of CD26 may be potentially linked to high topoisomerase II a level in selected T-cell malignancies, which are generally aggressive and often difficult to treat at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, topoisomerase II a is highly expressed on aggressive B-cell non-Hodgkin's lymphomas; on the other hand, its expression on T-cell malignancies appears to be generally low, although this conclusion is based on studies with limited samples (Holden et al, 1995;Turley et al, 1997;Korkolopoulou et al, 2001). Our current data with the human T-cell leukaemia cell line Jurkat suggest that the expression of CD26 may be potentially linked to high topoisomerase II a level in selected T-cell malignancies, which are generally aggressive and often difficult to treat at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…In each case, nuclei from 500 neoplastic cells from randomly selected fields of the whole section were counted and the Ki-S4 (topo IIa) and Ki-S5 (Ki-67) index was calculated as the percentage of positive nuclei. 26,27 All nuclear staining was counted as topo IIa ( Figures 1 and 2) or Ki-67 positivity. A hematological cell counter (Statitest L10, Ferrari, Berlin, Germany) was used for counting.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…26,27 The aim of this study was to gain more precise information about the topo IIa activity in MCL. We chose cases from two former large studies (1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985) with long follow-up data (up to 15 years) and in the majority of cases (around 90%) without a treatment containing topo inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Topoisomerase II ␣ (topo II ␣) is also a proliferation marker (12)(13)(14) and functions to prevent nondisjunction and chromosome breakage in mitosis (15,16). Topo II ␣ has been used recently to assess proliferative activity in neoplasms (12)(13)(14).…”
Section: Mod Pathol 2000;13(9):1014 -1019mentioning
confidence: 99%
“…Topo II ␣ is associated with cell proliferation (12)(13)(14) and functions in mitoses to prevent nondisjunction and chromosome breakage (15,16). Recent studies have indicated that topo II ␣ may have diagnostic or prognostic significance in a variety of tumors including gliomas (25), salivary gland adenoid cystic carcinomas (26), esophageal squamous cell carcinomas (27), gastric and colonic carcinomas (28), adrenal carcinomas (29), and thyroid carcinomas (30).…”
Section: Discusssionmentioning
confidence: 99%